PEMODELAN SKALA LABORATORIUM PENCEMARAN AIR TANAH OLEH LIMBAH MENGGUNAKAN METODE GEOLISTRIK - Wijayantari, Ida Ayu Meitri (JURNAL SPEKTRAN, 2019)
LABORATORY SCALE MODELING OF GROUNDWATER CONTAMINATION BY WASTE USING GEOELECTRIC METHOD ABSTRACT Research has been carried out with physical modeling using the geoelectric method to monitor the problem of water resources namely water pollution by waste. Pollution caused by industrial waste is a big problem, if the waste seeps into the soil and contaminates ground water consumed by humans, animals and other organisms. Decreasing groundwater quality can affect the fulfillment of community needs for clean water. Because the impact of industrial wastewater can not be directly felt, making people less aware of the dangers of waste that can pollute the presence of ground water. The purpose of this study was to identify the spread of liquid waste using the 2D type geoelectric method and find out the resistivity value. The tools used are type G-Sound Resistivity meter (GL-4100) and used liquid waste material used oil. Data processing was processed using RES2Dinv ver 3.3 software and obtained medium type resistivity values contaminated by liquid waste from geoelectric data of resistivity type was 0.962 - 12.4 ?m and from the geoelectric cross section (pseudosection) visible boundaries or areas contaminated with liquid waste contained in depth of 0 - 0.44 m from ground level (ground surface). On the results of data processing, there is a high value of species resistance, 44.5 - 84.3 m, which is interpreted as iron sand found in the clay sand medium used.